Selective Neuronal Vulnerability to Oxidative Stress in the Brain - Wang, Xinkun (Frontiers Research Foundation, 2010)
Oxidative stress (OS), caused by the imbalance between the generation and detoxification of reactive oxygen and nitrogen species (ROS/RNS), plays an important role in brain aging, neurodegenerative diseases, and other related adverse conditions, such as ischemia. While ROS/RNS serve as signaling molecules at physiological levels, an excessive amount of these molecules leads to oxidative modification and, therefore, dysfunction of proteins, nucleic acids, and lipids. The response of neurons to this pervasive stress, however, is not uniform in the brain. While many brain neurons can cope with a rise in OS, there are select populations of neurons in the brain that are vulnerable. Because of their selective vulnerability, these neurons are usually the first to exhibit functional decline and cell death during normal aging, or in age-associated neurodegenerative diseases, such as Alzheimer's disease. Understanding the molecular and cellular mechanisms of selective neuronal vulnerability (SNV) to OS is important in the development of future intervention approaches to protect such vulnerable neurons from the stresses of the aging process and the pathological states that lead to neurodegeneration. In this review, the currently known molecular and cellular factors that contribute to SNV to OS are summarized. Included among the major underlying factors are high intrinsic OS, high demand for ROS/RNS-based signaling, low ATP production, mitochondrial dysfunction, and high inflammatory response in vulnerable neurons. The contribution to the selective vulnerability of neurons to OS by other intrinsic or extrinsic factors, such as deficient DNA damage repair, low calcium-buffering capacity, and glutamate excitotoxicity, are also discussed.